MOOC’s Business Models: Turning Black Swans into Gray Swans - Aparicio, M.; Fernando Bacao; Oliveira, T. (ISDOC 2014, Proceedings of the International Conference on Information Systems and Design of Communication, 2014)
Massive open online courses (MOOCs) are black swans. A black swan is an unexpected event that emerges from reality and alters the reality itself. MOOCs have affected supply and demand in higher education. MOOCs distribute knowledge, classes on many areas of expertise for free. Millions of users, from all over the world are enrolling MOOCs courses. Universities are sharing resources and knowledge in the Internet no matter who or why. This paradigm shift has an impact on people’s life. So, how can universities survive if they are giving knowledge for free? This paper presents a literature review on MOOCs. We also modulate this reality to minimize the jeopardy and maximize the good opportunities that MOOCs bring.